1988
DOI: 10.1042/bj2490333
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 and a lactogen regulate proliferation and protein phosphorylation in Nb2 cells

Abstract: Cell proliferation and protein phosphorylation in response to activation of lactogenic and interleukin 2 (IL-2) receptors were studied in Nb2 cells, a rat T-lymphocyte cell line. Human growth hormone (hGH) and rat IL-2 stimulated Nb2-cell proliferation to approximately the same degree, and the actions of both mitogens were potentiated by phorbol 12-myristate 13-acetate (PMA). A monoclonal antibody specific for the rat IL-2 receptor inhibited the mitogenic actions of rat IL-2, but not those of hGH. Exposure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Nb2 cells were labelled with [ 32 P]-orthophosphate (TPA PRL) as described (Rayhel et al 1988, Fulton et al 1999, with modifications. Briefly, quiescent Nb2 cells (10 10 6 per treatment) were pelleted at 200 g for 5 min at room temperature, washed twice with phosphate-free RPMI 1640 (Life Technologies, Burlington, Ontario, Canada) and resuspended in 5 ml of the same medium for a 1-h incubation at 37 C. Cells were incubated with [ 32 P]-orthophosphate (0·1 mCi/ml) for 70 min at 37 C. TPA (20-80 nM) PRL (10 ng/ml) was added and inactive phorbol 4 -PHR (40 nM) was used as negative control.…”
Section: [ 32 P]-orthophosphate Labelling and Phosphoamino Acid Analysismentioning
confidence: 99%
“…Nb2 cells were labelled with [ 32 P]-orthophosphate (TPA PRL) as described (Rayhel et al 1988, Fulton et al 1999, with modifications. Briefly, quiescent Nb2 cells (10 10 6 per treatment) were pelleted at 200 g for 5 min at room temperature, washed twice with phosphate-free RPMI 1640 (Life Technologies, Burlington, Ontario, Canada) and resuspended in 5 ml of the same medium for a 1-h incubation at 37 C. Cells were incubated with [ 32 P]-orthophosphate (0·1 mCi/ml) for 70 min at 37 C. TPA (20-80 nM) PRL (10 ng/ml) was added and inactive phorbol 4 -PHR (40 nM) was used as negative control.…”
Section: [ 32 P]-orthophosphate Labelling and Phosphoamino Acid Analysismentioning
confidence: 99%
“…It is generally believed that many of the actions of cAMP in eukaryotic cells are mediated through protein kinases; accordingly, Nb2 cell proteins phosphorylated in response to 8-Br-CAMP and PRL were analyzed by two-dimensional gel electrophoresis and autoradiography. Cells were exposed to test agents for 4 h, because previous studies [9,14] have demonstrated changes in protein phosphorylation after exposure of Nb2 cells to PRL for 3 4 h. In the absence of 8-Br-cAMP, PRL decreased incorporation of radioactive phosphate into four proteins with PIS of approximately 5.7 and MWs ranging from 3 1,000 to 48,000 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The second dimension was sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (4% stacking gel, 5-20% linear-gradient separating gel) as described by Laemmli [ 181. The gels were dried and autoradiographed as described previously [9]. Pre-stained protein markers (Bio-Rad) were used for molecular weight (MW) determinations.…”
Section: Protein Phosphorylation and Two-dimensional Gel Electrophoresismentioning
confidence: 99%
“…Binding of IL-2 to its high-affinity receptor rapidly activates intracellular processes that lead to gene activation and de novo gene transcription, DNA synthesis, and cell cycle progression (3)(4)(5)(6). Even though IL-2-toxin rapidly inhibits protein synthesis in IL-2R-bearing phytohemagglutinin (PHA)-activated T cells, we now note that this chimeric toxin also transiently stimulates DNA synthesis (e.g., thymidine incorporation).…”
mentioning
confidence: 99%
“…The mature form of IL-2-toxin has a deduced molecular mass of 68 kDa, and the fusion protein retains at least some functional attributes of both its diphtheria toxin and IL-2 components. The fusion protein (i) binds with high affinity to the multimeric IL-2 receptor (IL-2R), (ii) is internalized by IL-2R-mediated endocytosis, and (iii) mediates the ADP-ribosylation of elongation factor 2 in the target-cell cytosol (2).Binding of IL-2 to its high-affinity receptor rapidly activates intracellular processes that lead to gene activation and de novo gene transcription, DNA synthesis, and cell cycle progression (3)(4)(5)(6). Even though IL-2-toxin rapidly inhibits protein synthesis in IL-2R-bearing phytohemagglutinin (PHA)-activated T cells, we now note that this chimeric toxin also transiently stimulates DNA synthesis (e.g., thymidine incorporation).…”
mentioning
confidence: 99%